Perlindungan Hukum terhadap Konsumen dalam Perjanjian Baku di Indonesia - Moch Irfanur Khokim (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
A standard agreement is a form of standard contract that is drawn up unilaterally by business actors, without providing flexibility for consumers to negotiate the content of the clauses contained therein. This characteristic creates an imbalance in the legal position between business actors and consumers, which in practice is often used to include exculpation clauses or unilateral clauses that are substantively detrimental to consumers. In the context of Indonesian law, this form of contract has become a common practice in various sectors, ranging from financial services to electronic transactions, so the urgency of legal protection for consumers has become increasingly significant. This research aims to analyze and evaluate the form of legal protection for consumers in standard agreements, based on the provisions of Law Number 8 of 1999 concerning Consumer Protection and related legal instruments, including implementing regulations and relevant jurisprudence. The research approach used is normative juridistic, with data collection methods through literature studies, normative analysis of laws and regulations, and an examination of several concrete case studies that illustrate imbalances in the legal relationship between consumers and business actors. The results of the study revealed that although normative legal protection has been regulated quite firmly, especially in the provisions regarding the prohibition of the inclusion of clauses that are detrimental or misleading to consumers, various structural and cultural obstacles are still found in its implementation. These obstacles include weak supervision mechanisms for business actors, limited consumer access to legal understanding, and suboptimal role of consumer dispute resolution institutions. Thus, it is necessary to strengthen regulations through more operational legal instruments, increase the capacity of supervisory institutions, and mainstream consumer legal literacy as a long-term strategy in realizing a fair, effective, and sustainable consumer protection system.